Máquinas semeadoras pneumáticas: confecção de vácuo-compressor para acionar dosadores de sementes - Maia, Roberto Nunes (2022)
The modernization of equipment developed for agriculture is a fundamental factor to increase grain production. Seeders are of great importance for increasing productivity and it is necessary to develop equipment capable of producing vacuum and compressed air. Therefore, the objective was to develop a vacuum-compressor and three heads with peculiar specifications and then compare them, taking into account the main variables involved in the sowing process. The work was developed in the laboratory of thermal machines of the Federal Institute of Ceará - IFCE, Campus de Limoeiro do Norte-CE. The data collected come from 15 (fifteen) speed ranges (140, 240, 340, 440, 540, 640, 740, 840, 940, 1040, 1140, 1240, 1340, 1440 and 1540 rpm), with five repetitions each. Data were collected on the following variables: crankshaft rotation, air speed, negative pressure (vacuum), positive pressure (compressed air) and electric current (amperage). All versions of heads (CV1, CV2 and CV3) produced the necessary vacuum to perform the sowing activity of the bean cultivar. The CV1 at 1,540 rpm displaces 2,028 liters of air per minute in the suction, being able to drive three seeding lines with energy consumption of 6.51 CV. With the same rotation, the CV2 displaces 1,142 liters of air per minute in the suction and 781 liters in the discharge, with an energy consumption of 6.44 CV. CV2, experiment 4, with rotation of 140 rpm, suction pressure (vacuum) set at 26.67 KPa, discharge flow of 100 liters of air per minute and energy consumption of 3.96 CV. Observing only the intensity of vacuum production, the equipment would trigger 11 sowing lines. At 940 rpm, the CV3 produces a suction pressure (vacuum) of 3.71 KPa, with an energy consumption of 1.28 CV, providing 2.90 KPa of vacuum for each CV. It is worth mentioning that the vacuum-compressor equipment was activated with an electric motor of 5.5 KW (7.5 CV) on a laboratory bench and that for sowing activity it will be activated by the tractor TDP, thus having a wide margin of power availability for drive. As the vacuum-compressor block is quite robust, it allows that in seeding operation, the crankshaft rotation reaches values tripled of those that were tested, in addition, if versions of heads are made using electronic commands to perform the opening and closing of the valves and suction and discharge, the efficiency will be increased.